Aprendizaje Basado en Proyectos y su influencia en los Procesos Atencionales en los estudiantes de 4to año de EGB de la escuela Oswaldo Guayasamín, Quevedo 2022 - Reyes Gender, Irene Mirella (2023)
This master's thesis addresses the importance of pedagogical strategies in the application of the Project-Based Learning methodology, as a technique for improving the attentional process of students. Since, one of the factors that limits learning is the little attention to the class that the teacher teaches in the classroom, in view of this, applied techniques and strategies have shown to be a strategy that allows students to be motivated and therefore to be concentrated. in educational activities. The main objective of the research is to determine the influence that PBL has on the attentional process. The research has as study population the fourth grade students of the Oswaldo Guayasamín school in the City of Quevedo, the selected sample corresponds to 71 students, to whom the questionnaire instrument was applied through the survey technique, the The instrument was validated for reliability. Among the main results, it stands out that the students show an interest in using the activities that involve them directly. The PBL methodology significantly affects the attentional process, in such a way that each time it is used, the students show interest in the class. Finally, it is concluded that every time students work with learning methods different from the traditional ones, they show interest in knowing the new way of learning. The ABP improves the attentional process in fourth grade students, because they have a high interest in learning new things.